Commercial orchids (2014)
Orchids comprise the largest family of flowering plants with 25,000 to 35,000 species belonging to 600-800 genera and cover 10% of the flowering plants. They are prized for their incredible diversity in size, shape and colour and attractiveness of their flowers and high keeping qualities even up to 10 weeks. Most orchids originated in the tropical humid forests of Central and South America, India, Sri Lanka, Burma, South China, Thailand, Malaysia, Philippines, New Guinea and Australia. Brazilian Cattleya, Mexican Laelia and Indian Cymbidium, Vanda and Dendrobium have played a major role in developing present day beautiful hybrid orchids, which number more than 200,000. In international trade, among the top ten cut flowers, orchids rank as sixth and among orchids Cymbidium claims the first position, accounting for 3% of the total cut flower production in floricultural crops. Orchids are found in nearly every environment in the world starting from tropical and subtropical to alpine zones, both epiphytically and terrestrially.